The Fragments of the Frescoes from the Burial Church in St. Euphrosyne’s Convent in Polotsk (from the Funds of the Novgorod State Museum) - Skobtsova, Darya A. (Actual Problems of Theory and History of Art, 2013)
The mural paintings of the destroyed burial church in Polotsk have survived only fragmentally. These fresco fragments were discovered in the 1960’s by the archeological expedition headed by M. Karger. There are fragments of ornament, imitation of marble panels, garments and faces. Small scale faces undoubtedly belong to one painting ensemble and they were created at one time. Probably we may date the fresco fragments to the 1120’s or 1130’s. These images have some common features with the murals of the Christ Transfiguration church in Polotsk. So this can testify to the original artistic tradition of this region.
Keywords: Old Russian art; mural painting; fragments of frescoes; Polotsk